The little data book on financial inclusion. (Online access: World Bank World Bank Open Knowledge Repository., 2015)
A pocket edition of the Global Financial Inclusion Database published in 2015 in The Global Findex Database 2014: Measuring Financial Inclusion around the World? by Asli Demirguc-Kunt, Leora Klapper, Dorothe Singer, and Peter Van Oudheusden (World Bank Policy Research Paper 7255). It provides 41 country-level indicators of financial inclusion summarized for all adults and disaggregated by key demographic characteristics-- gender, age, income, and rural residence. The book also includes summary pages by region and by income group aggregates. Covering 143 economies, the indicators of financial inclusion measure how people save, borrow, make payments and manage risk.